2002
DOI: 10.1124/mol.61.5.1033
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Phosphodiesterase 3 Activity and Phosphodiesterase 3A Level in Synthetic Vascular Smooth Muscle Cells: Implications for Use of Phosphodiesterase 3 Inhibitors in Cardiovascular Tissues

Abstract: Vascular smooth muscle cells (VSMC) in situ function to control contraction and are said to express a contractile phenotype. However, during development or in response to vascular damage, VSMC proliferate and express a more synthetic phenotype. A survey of literature values for contractile and synthetic VSMC phosphodiesterase (PDE) 3 and PDE4 activities identified a marked difference in the PDE3 and PDE4 activities of these cells. In this study, a comparison of PDE3 and PDE4 activities in contractile and synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 41 publications
5
31
1
Order By: Relevance
“…First, our finding that PDE3 and PDE4 activities accounted for 50 and 35% of cAMP PDE activity in rat arteries, respectively, was different from our earlier reports, in which we showed that PDE3 and PDE4 activities represented 20 and 65% of cAMP PDE activity, respectively, in cultured rat aortic VSMC (Rose et al, 1997;Liu and Maurice, 1999;Liu et al, 2000). Recently, we showed that these differences were caused by a marked decrease in PDE3A upon culturing of these cells and that a similar reduction occurred when VSMC were activated in response to vascular injury in vivo (Dunkerley et al, 2002). Second, although the results of our study provide evidence that cAMP-elevating agents increased aortic and femoral artery VSMC PDE3 and PDE4 activities, the overall magnitude of the increases in vivo were significantly smaller than those achieved in cultured rat or human aortic VSMC (Rose et al, 1997;Liu et al, 2000).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…First, our finding that PDE3 and PDE4 activities accounted for 50 and 35% of cAMP PDE activity in rat arteries, respectively, was different from our earlier reports, in which we showed that PDE3 and PDE4 activities represented 20 and 65% of cAMP PDE activity, respectively, in cultured rat aortic VSMC (Rose et al, 1997;Liu and Maurice, 1999;Liu et al, 2000). Recently, we showed that these differences were caused by a marked decrease in PDE3A upon culturing of these cells and that a similar reduction occurred when VSMC were activated in response to vascular injury in vivo (Dunkerley et al, 2002). Second, although the results of our study provide evidence that cAMP-elevating agents increased aortic and femoral artery VSMC PDE3 and PDE4 activities, the overall magnitude of the increases in vivo were significantly smaller than those achieved in cultured rat or human aortic VSMC (Rose et al, 1997;Liu et al, 2000).…”
Section: Discussioncontrasting
confidence: 53%
“…Previous published work by our group (Liu and Maurice, 1998;Palmer and Maurice, 2000;Dunkerley et al, 2002), and results shown here (Fig. 1), demonstrate that the vast majority (Ͼ90%) of cells in rat aorta, or rat femoral artery, once cleaned of adherent connective tissue and fat, are medial VSMC.…”
Section: Resultsmentioning
confidence: 66%
“…Serum starvation has been shown to modulate the phenotype of VSMCs from a synthetic/activated to a contractile/quiescent state (Li et al, 1999), a process known to involve chromatin remodeling, which adds credence to the notion that increased acetylation of CREs in the promoters of PDE4 genes can direct their transcription. It is interesting that the data presented here, in combination with our previous report demonstrating loss of PDE3A expression in rat synthetic/activated VSMCs (Dunkerley et al, 2002) and earlier reports of reduced soluble guanylyl cyclase and protein kinase G expression in synthetic/activated VSMCs (Anderson et al, 2000), may point to a more general phenotype-mediated reorganization of cyclic nucleotide signaling in these cells. Although provocative, the overall role that differential histone acetylation of the promoters controlling the expression of PDE3A, soluble guanylyl cyclase, and protein kinase G may play in these events remains to be assessed.…”
Section: Discussionsupporting
confidence: 50%
“…A7r5 cells natively express only Kv7.5 channels (Brueggemann et al, 2007, whereas MASMCs predominantly express Kv7.4/Kv7.5 channels (Brueggemann et al, , 2014a. Insensitivity of MASMC Kv7.4/7.5 channels to rolipram was replicated when this same subunit combination was expressed in A7r5 cells, suggesting that the difference in regulation of native Kv7 currents between A7r5 cells and MASMCs relates primarily to the Kv7 channel subunit stoichiometry rather than to differences in PDE isoforms (Polson and Strada, 1996;Dunkerley et al, 2002;Maurice et al, 2003).…”
Section: Discussionmentioning
confidence: 83%